Tigecycline for Extensively Drug-Resistant Typhoid: In vitro Evidence and Clinical Relevance - Samaha Khalid (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Salmonella enterica serovar Typhi, a Gram-negative bacillus causing enteric fever, poses an increasing global health threat due to rising antimicrobial resistance (AMR). The emergence of extensively drug-resistant (XDR) strains, resistant to nearly all first- and second-line antibiotics, has left azithromycin and carbapenems as the last remaining options. This study evaluates the in vitro susceptibility of XDR S. Typhi to tigecycline, a broad-spectrum agent effective against multidrug-resistant pathogens, to inform treatment choices and strengthen resistance surveillance. Objectives: To evaluate the in vitro susceptibility of XDR S. Typhi isolates to tigecycline. To assess tigecycline’s potential role as an alternative treatment when azithromycin or meropenem are ineffective. To highlight emerging resistance trends in XDR S. Typhi. Methods: This retrospective cross-sectional study was conducted at Fauji Foundation Hospital, Rawalpindi, from July 2023 to June 2024. A total of 99 XDR S. Typhi blood culture isolates were analysed from patients aged 1–70 years, selected through consecutive non-probability sampling. Identification was confirmed using API 20E. Among these, 60 isolates underwent tigecycline susceptibility testing using EUCAST disk diffusion using Mueller-Hinton agar. Since specific breakpoints are lacking for S. Typhi, non-species-related breakpoints were applied. Data analysis was performed using SPSS v27.0. Results: Of the 99 XDR S.Typhi blood culture isolates that were obtained, paediatrics accounted for 57.6%, medicine for 29.3%, and surgery for 13.1%. Males made up 56.6%, with the 1–10 age group predominating (47.5%) and followed by the 11–20 age group (31.3%). 2024 had a peak in infections in April (18.2%) and May (17.2%). The XDR status was confirmed by the fact that all isolates were resistant to ampicillin (66.7%), ceftriaxone (69.6%), chloramphenicol (79.4%), ciprofloxacin (78.4%), and co-trimoxazole (77.4%). In addition to imipenem (100%, n=80) and meropenem (100%, n=59), tigecycline demonstrated 100% susceptibility (n=60), demonstrating its effectiveness against XDR S. Typhi. Conclusion: Tigecycline exhibited complete in vitro efficacy against XDR S. Typhi isolates, supporting its potential role in managing resistant infections, especially among pediatric cases. Maintaining the utility of last-line agents demands strong antimicrobial stewardship and further research into resistance mechanisms and optimized dosing in resource-limited settings. Keywords: Extensively Drug-Resistant (XDR) Typhoid, Tigecycline, Salmonella Typhi, Antimicrobial Resistance (AMR), In vitro Susceptibility